Implementation of Diversity Management in Decision Making at PT Coca Cola Europacific Partners Indonesia Pekanbaru Branch - Yudi Handika; Andreo Wahyudi Atmoko (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper explores situations of diversity and leadership policies. Diversity and making decisions will be very influential. This is inseparable from the emergence of various ideas resulting from diversity at PT Coca Cola Europacific partnership. Diverse employees create many inputs and ideas that form the basis for the company's decision making. In practice, PT Coca Cola Europacific Partnership also found many obstacles. With a qualitative approach and through interview techniques, the researchers tried to obtain information related to diversity at PT Coca Cola Europacific Partnership. Findings show that by managing diversity will be very influental in making decisions. Therefore, researchers provide recommendations to be able to make diversity a source of progress for organizations.